Corrosion-Resistant High-Entropy Alloys: A Review - Yunzhu Shi; Bin Yang; Peter K. Liaw (Metals, 2017)
Corrosion destroys more than three percent of the world’s gross domestic product. Therefore, the design of highly corrosion-resistant materials is urgently needed. By breaking the classical alloy-design philosophy, high-entropy alloys (HEAs) possess unique microstructures, which are solid solutions with random arrangements of multiple elements. The particular locally-disordered chemical environment is expected to lead to unique corrosion-resistant properties. In this review, the studies of the corrosion-resistant HEAs during the last decade are summarized. The corrosion-resistant properties of HEAs in various aqueous environments and the corrosion behavior of HEA coatings are presented. The effects of environments, alloying elements, and processing methods on the corrosion resistance are analyzed in detail. Furthermore, the possible directions of future work regarding the corrosion behavior of HEAs are suggested.